Kyanite-bearing anatectic metapelites from the Eastern Himalayan Syntaxis, Eastern Tibet, China : textural evidence for partial melting and phase equilibria modeling - Guilmette, Carl; Aphrodite, Indares; Réjean, Hébert; Wang, CS (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1258 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.56